2014
DOI: 10.4311/2013lsc0100
|View full text |Cite
|
Sign up to set email alerts
|

Diet Analysis of Leopoldamys Neilli, a Cave-dwelling Rodent in Southeast Asia, Using Next-Generation Sequencing from Feces

Abstract: Leopoldamys neilli is a Murinae rodent endemic to limestone karst of Thailand and the Lao PDR, but its ecology and the reasons of its endemism to karst are still totally unknown. The aim of this pilot study was to examine the plant composition of the diet of L. neilli at the level of order and family using DNA for molecular identification and to compare it with two other forest-dwelling Leopoldamys species, L. herberti and L. sabanus. A 202bp fragment of the rbcL gene was amplified and sequenced for twenty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Digestion pass-through rates, for example, can be quite rapid in other rodent species and experimental studies have reported rates ranging from 0.5–13 hours [51, 52]. Soininen et al [50] reported high variability in recovered diet components among individual fecal samples from two small voles ( Microtus oeconomus and Myodes rufocanus ), and high fecal-sample variability has been reported elsewhere [62, 63]. Nonetheless, we expect population-level comparisons based on large samples to be robust to intra-individual noise.…”
Section: Discussionmentioning
confidence: 99%
“…Digestion pass-through rates, for example, can be quite rapid in other rodent species and experimental studies have reported rates ranging from 0.5–13 hours [51, 52]. Soininen et al [50] reported high variability in recovered diet components among individual fecal samples from two small voles ( Microtus oeconomus and Myodes rufocanus ), and high fecal-sample variability has been reported elsewhere [62, 63]. Nonetheless, we expect population-level comparisons based on large samples to be robust to intra-individual noise.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of visual diet analysis cannot be ignored, especially when we want to know exactly which prey part the predator is consuming (Latinne et al 2014) or to quantify predation. In this study, with visual identification we found that seeds were the most commonly eaten plant part in the diet of the 3 pest species.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several diets based on faeces of a broad panel of mammal species encompassing herbivores, bats, carnivores, and rodents among others, have been successfully analyzed with molecular techniques using DNA barcoding (Soininen et al 2009;Zeale et al 2011;Galan et al 2012;Shehzad et al 2012;Latinne et al 2014). The different prey species and plant taxa contained in the faeces are identified by amplifying small and highly variable DNA fragments with universal primers and by using them as barcodes.…”
Section: Introductionmentioning
confidence: 99%